Desain Sistem Kerja Bongkar Muat Menggunakan Metode Fisiologi dan Biomekanika pada Serikat Pekerja Seluruh Indonesia Kota Banda Aceh - Arhami Arhami (Jurnal Teknik Mesin, 2022)
Load loading activity is a work condition where heavyweight causes excessive energy on working position so that the potential of musculoskeletal complaints and early fatigue disorder occur. Early fatigue can possibly cause illness and accidents which lead to disability and perhaps death. This study aims to produce a supporting design tool for work on load loading activities based on biomechanics and physiology methods regarding workers of the Serikat Pekerja Seluruh Indonesia (SPSI) Banda Aceh, Indonesia. A normal lift restriction is provided by the National Institute of Occupational Safety and Health (NIOSH) consist of a range of aspects of biomechanics and physiology. Biomechanical limitations include the magnitude compression force at 3.4 kN (770 lbs) and physiological limitations include the energy expenditure to a maximum of 2.2 to 4.7 kcal/minutes. Steps and stages processes are taken in the physiology method begun by recording workers’ heart rate/pulse before work while working and at rest. The next stage was calculated workers’ energy expenditure, at the time before work it was at 2,815 kcal/minutes while working at 8.194 kcal/min, and while at rest it was at 5.58 kcal/min. The researcher also calculated the energy consumption of each worker in about 2,614 kcal/min. The measurement of biomechanics method is the measurement of the Recommended Weight Limit (RWL) origin and destination absence supporting tools, and then calculated the lifting index (LI) origin and destination value without supporting work tools. The LI origin was 2.9 and 2.3 to 2.6 destination. So according to LI criteria values were above 1 point which indicated that works were not safe and potentially could cause injury. The value of RWL origin and destination using supporting tools able to count the LI origin and destination value on the condition of using supporting tools, a value obtained was 0.825 LI origin and destination 0.38 to 0.44. It showed the workers were safely done. The conclusion of all stages test conducted in this study is to provide design support tools as a solution for load loading work which allows the slider conveyor concept to move materials from the place of its origin to its destination.